Heart Disease : Environment, Stress and Gender. - Kopp, M. S. (NATO science series. Life and behavioural sciences, 2002)
This text attempts to answer the question: Why do men get more heart disease than women? The book focuses on environmental, behavioural, and psychosocial variables, as well as new risk factors of a biological nature in an attempt to understand the gender gap in heart disease.